In vitro CYP-mediated drug metabolism in the zebrafish (embryo) using human reference compounds. (August 2017) - Saad, Moayad; Matheeussen, An; Bijttebier, Sebastiaan; Verbueken, Evy; Pype, Casper; Casteleyn, Christophe; Van Ginneken, Chris; Apers, Sandra; Maes, Louis; Cos, Paul; Van Cruchten, Steven
Abstract: The increasing use of zebrafish embryos as an alternative model for toxicological and pharmacological studies necessitates a better understanding of xenobiotic biotransformation in this species. As cytochrome P450 enzymes (CYPs) play an essential role in this process, in vitro drug metabolism of four human CYP-specific substrates, i.e. dextromethorphan (DXM), diclofenac (DIC), testosterone (TST) and midazolam (MDZ) was investigated in adult male and female zebrafish, and in zebrafish embryos and larvae up to 120 hours post-fertilization. Substrate depletion and production of their respective metabolites were measured using tandem quadrupole UPLC-MS/MS. Human liver microsomes were used as positive control. Adult zebrafish produced the two major human metabolites of DIC and DXM. For DIC the metabolite ratio was similar to that in man, whereas it was different for DXM. For TST, the major human metabolite could not be detected and MDZ was not metabolized. No sex-related differences were detected, except for the higher TST depletion rate in adult females. Zebrafish embryos and larvae showed no or only low biotransformation capacity. In conclusion, in vitro CYP-mediated drug metabolism in adult zebrafish shows differences compared to man and appears to be lacking in the early zebrafish life stages. As CYP-mediated drug metabolism in zebrafish may not be predictive for the one in man, we recommend including the zebrafish in metabolic stability testing of new compounds when considering non-clinical species for human risk assessment. Highlights: CYP activity in zebrafish has similarities but also differences compared to man. Zebrafish embryos have a much lower CYP activity compared to adults. Drug risk assessment in zebrafish necessitates metabolic stability test.